Oral sex and oral cancer in the context of human papillomavirus infection: lay public understanding - Mario A. Brondani; Mario A. Cruz-Cabrera; Cheryle Colombe (Frontiers Media S.A., 2011)
Human papillomavirus (HPV) is a risk factor for ano-genital and cervical cancers and has been associated with head and neck malignancies in the context of oral sex for the transmission of the virus. However, the level of knowledge that lay people have in terms of HPV transmission through oral sex and oral cancer development remains unknown. A pilot sample of 150 questionnaires was distributed at specific non-profit health organizations in Vancouver, Canada. Questions included perceived risks for oral sex in terms of HPV infection and oral cancer development, and the frequency with which respondents were asked about oral sexual practices by physicians and dentists. Data were analysed statistically by age group (19- 30, 31-50, 50\), gender (male, female), and sexual orientation (queer, straight). 110 questionnaires were returned fully completed. For the transmission of HPV, 58% of the participants believed that oral sex is an activity of no or low risk, whereas 72% considered the same activity to be of no risk for the development of oral cancer. There was no statistical difference between gender and sexual orientation. Participants never discussed related health risks in regard to oral sex with their physicians or dentists. In conclusion, although recent attention has been given to the potential links between HPV infection and oral cancer, such links remain mostly unknown by the public. Physicians and dentists could discuss oral sex practices to raise awareness with their patients. This is a small sample size study and the results should be interpreted with caution.